Research on the Impact of Marketing Strategy on Consumers’ Impulsive Purchase Behavior in Livestreaming E-commerce - Chen, Bing; Wang, Lei; Rasool, Hassan; Wang, Jun (Frontiers in Psychology, 2022)
Live streaming e-commerce has emerged as a highly profitable e-commerce that has revolutionized the retail industry, especially during the COVID-19 pandemic. However, research on live streaming e-commerce is still in its infancy. The current study sheds new light on impulsive purchase behavior in live streaming e-commerce. Based on SOR theory, this study introduces the ‘People-Product-Place’ marketing strategy for live streaming e-commerce from the perspective of consumer perception, and aims to understand the impact of marketing strategy on impulsive purchase behavior in e-commerce live streaming shopping scenes, and to examine the mediating effect of involvement. The study conducted SEM analysis, in Amos, on 437 response sets from an online anonymous survey. The results show that perceived e-commerce anchor attributes, perceived scarcity and immersion positively influence impulsive purchase behavior; that ‘People-Product-Place’ marketing strategy is important; and that effective marketing triggers impulsive purchase. Perceived e-commerce anchor attributes, perceived scarcity and immersion positively influence involvement, which positively influences impulsive purchase. Involvement mediates between perceived e-commerce anchor attributes, perceived scarcity and immersion and impulsive purchase. These findings guide marketers to improve the profitability of live streaming e-commerce, and provide some references of economic recovery for many other countries which also suffered from the impact of COVID-19 pandemic.